Innu and Naskapi materials, Miscellaneous Manuscripts Collection - Harper, Francis, 1886-1972 (1953)
Lists of Montagnais names of birds, fishes and amphibians, and mammals. Based on French-speaking informants, Sebastian McKenzie and his son Francis, Scotch-Montagnais descent. Orthography is French, not phonetic. Secured during Ungava expedition of the Arctic Institute of North America.